Интеллектуальная система управления электроимпульсными установками - Козырев, С.С.; Овчинникова, Л.Е. (Технічна електродинаміка, 2012)
The intellectual automated control system, based on fuzzy-logic, was developed for the electropulse installations. The neuronet controller was used for membership function parameters correction in a process of operation. Also a rule base is dynamically synthesized using a neuron network.